Sustainable urban development in Latin America - Christian Juan Murillo Delgado; Adriana Carolina Calderon Munoz; Hugo Jose Icaza Valencia; Lizeth Carolina Sanchez Bazantes (Universidad Ciencia y Tecnología, 2023)
This paper shows the results of a documentary exploration of sustainable development in Latin America. The Latin American region is characterized by having holistic environmental policies, but it is also integrated and seeks to balance economic growth, social inclusion, and environmental preservation. For this work, different reliable sources have been analyzed to know the Latin American trends around the subject and specify the strategies that must be addressed to achieve the expected results. In this sense, a program is proposed that aims to strengthen environmental awareness and promote sustainable urban planning practices in rural communities in Latin America. The main results show that environmental education empowers local communities to become agents of change and adopt sustainable measures in natural resource management, agriculture, energy, and environmental conservation.